Large contribution from worship activities to the atmospheric soot particles in northwest China. (15th April 2022) - Lin, Chunshui; Huang, Ru-Jin; Duan, Jing; Zhong, Haobin; Xu, Wei; Wu, Yunfei; Zhang, Renjian
Abstract: Worship activities like burning joss paper during the Chinese Hanyi festival is a common, traditional custom in northwest China. However, the pollutants of e.g., soot particles, released from joss paper burning and the corresponding impacts on urban air quality were poorly investigated, which can be a particular concern since these activities are conducted in an uncontrolled manner. In this study, a long time-of-flight (LToF) soot particle aerosol mass spectrometry (SP-AMS) was deployed to characterize the refractory black carbon (rBC) emitted from the joss paper burning, as well as crop residue, coal combustion, and traffic during the Hanyi Festival in mid-November 2020 in the northwestern city of Xi'an in China. Large difference (from <5% to >100%) in the fragmentation patterns (Cn + ) for the measured rBC from different source emissions were found when compared to the reference Regal Black. Using the receptor model of positive matrix factorization (PMF) with the multilinear engine (ME-2) algorithm, the obtained rBC mass spectra were used as the anchoring profiles to evaluate the emission strengths of different source types to the atmospheric rBC. Our results show that the burning of joss paper accounted for up to 42% of the atmospheric rBC mass, higher than traffic (14–17%), crop residue (10–17%), coal (18–20%) during the Hanyi festival in northwest China. Moreover, we show that the overall air quality can be worsened due to the practice of uncontrolled burning of joss paper during the festival, which is not just confined to the people who do the burning. Although worship activities occur mainly during festival periods, the pollution events contributed by joss paper burning may pose an acute exposure risk for public health. This is particularly important since burning joss paper during worship activities is common in China and most Asian countries with similar traditions. Graphical abstract: Image 1 Highlights: Direct emissions of BC from different sources are characterized and inter-compared. Different emission sources showed different fragmentation patterns for Cn + . Emissions from worship activities are non-negligible during the festival period. BC contribution from Joss paper burning are found be higher than traffic. Overall air quality is worsened due to the practice of uncontrolled burning activity.